Effects of Gender and Age at Diagnosis on Disease Progression in Long-term Survivors of Cystic Fibrosis - Nick, Jerry A.; Chacon, Cathy S.; Brayshaw, Sara J.; Jones, Marion C.; Barboa, Christine M.; Clair, Connie G. St; Young, Robert L.; Nichols, David P.; Janssen, Jennifer S.; Huitt, Gwen A.; Iseman, Michael D.; Daley, Charles L.; et al. (American journal of respiratory and critical care medicine, 2010)
Long-term survivors of cystic fibrosis (CF) (age > 40 yr) are a growing population comprising both patients diagnosed with classic manifestations in childhood, and nonclassic phenotypes typically diagnosed as adults. Little is known concerning disease progression and outcomes in these cohorts. Examine effects of age at diagnosis and gender on disease progression, setting of care, response to treatment, and mortality in long-term survivors of CF. Retrospective analysis of the Colorado CF Database (1992-2008), CF Foundation Registry (1992-2007), and Multiple Cause of Death Index (1992-2005). Patients with CF diagnosed in childhood and who survive to age 40 years have more severe CFTR genotypes and phenotypes compared with adult-diagnosed patients. However, past the age of 40 years the rate of FEV(1) decline and death from respiratory complications were not different between these cohorts. Compared with males, childhood-diagnosed females were less likely to reach age 40 years, experienced faster FEV(1) declines, and no survival advantage. Females comprised the majority of adult-diagnosed patients, and demonstrated equal FEV(1) decline and longer survival than males, despite a later age at diagnosis. Most adult-diagnosed patients were not followed at CF centers, and with increasing age a smaller percentage of CF deaths appeared in the Cystic Fibrosis Foundation Registry. However, newly diagnosed adults demonstrated sustained FEV(1) improvement in response to CF center care. For patients with CF older than 40 years, the adult diagnosis correlates with delayed but equally severe pulmonary disease. A gender-associated disadvantage remains for females diagnosed in childhood, but is not present for adult-diagnosed females.